2011
DOI: 10.1007/s00228-010-0979-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic and pharmacokinetic drug interactions reported to VigiBase, the WHO global individual case safety report database

Abstract: Objective: Drug interactions resulting in adverse drug reactions (ADRs) represent a major health problem both for individuals and the community. Despite this, there is limited information in the literature regarding drug interaction categories responsible for causing ADRs.In this study we investigated the drug combinations most frequently co-reported as interacting in the WHO Global Individual Case Report (ICSR) Database, VigiBase, and categorised them in respect to the drug interaction mechanism. Methods: Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…However, drugs frequently cause side effects and drug related problems (DRPs) are a common cause for patients' suffering and substantial costs for society [1][2][3][4]. A significant part of DRPs can be prevented if health care personnel and patients have the necessary knowledge or information in a usable form when needed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, drugs frequently cause side effects and drug related problems (DRPs) are a common cause for patients' suffering and substantial costs for society [1][2][3][4]. A significant part of DRPs can be prevented if health care personnel and patients have the necessary knowledge or information in a usable form when needed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…We were surprised to find that the predicted areas under concentration–time curves were poorly correlated with the overall RR SB estimates, considering that inhibition of cytochrome P450s is thought to be the most common mechanism underlying known, clinically important drug–drug interactions 11 . There are at least five potential explanations for the poor correlation.…”
Section: Discussionmentioning
confidence: 97%
“…10 Inhibition of drug metabolism, and that mediated by cytochrome P450 enzymes in particular, is the most common mechanism underlying known, clinically important drug–drug interactions. 11 In a drug–drug interactions occurring via this mechanism, the object drug (e.g. sulfonylureas) is the drug whose metabolism is inhibited, and the precipitant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The reports from the WHO Drug Monitoring Programme are collected in VigiBase, and several recent studies point to important applications of this database. An investigation of reporting patterns indicative of ADR, as suspicion of pharmacokinetic interactions (where carbamazepine was the only AED mentioned) or hepatotoxicity, was conducted . Recently, an exploratory study was published investigating ADR in children reported from 97 countries…”
Section: Surveillance Of Adrs With Aedsmentioning
confidence: 99%